Efektivitas Media Poster, Video Animasi dan Podcast terhadap Pengetahuan Remaja Mengenai Diabetes - Sapitri, Vira; Kurniasari, Ratih (Universitas Muhammadiyah Semarang, 2024)
Background: Diabetes mellitus is a metabolic disease due to problems in insulin production. Less insulin produced by the pancreas results in an imbalance of sugar in the blood. Diabetes mellitus is one of the serious diseases that we must prioritize, especially for the prevention of diabetes mellitus, especially to prevent it, one of which is by conducting education using innovative media. Objectives: The purpose of this study was to determine how effective the dissemination of information about diabetes mellitus through the media of posters, animated videos and podcas. Method: This type of study is called a quasi-experimental pretest-posttest. The study sample was 45 people. By using a questionnaire consisting of 20 questions. Test analysis using paired sample t-test. Results:This study showed that respondents' knowledge before and after education using poster media, animated videos and podcasts increased with each p-value of 0.001. Conclusion: posters, animated videos, and podcasts effectively increase adolescents' knowledge about diabetes mellitus. Keyword : Diabetes Mellitus, Education, Podcast, Poster, Video Animation